Clinical and molecular characterization of Acinetobacter seifertii in Taiwan. (31st October 2020) - Li, Li-Hua; Yang, Ya-Sung; Sun, Jun-Ren; Huang, Tzu-Wen; Huang, Wei-Cheng; Chen, Feng-Jui; Wang, Yung-Chih; Kuo, Ting-Hao; Kuo, Shu-Chen; Chen, Te-Li; Lee, Yi-Tzu; ,
Abstract: Objectives: Acinetobacter seifertii, a new member of the Acinetobacter baumannii group, has emerged as a cause of severe infections in humans. We investigated the clinical and molecular characteristics of A. seifertii . Patients and methods: This retrospective study enrolled 80 adults with A. seifertii bloodstream infection (BSI) at four medical centres over an 8 year period. Species identification was confirmed by MALDI-TOF MS, rpoB sequencing and WGS. Molecular typing was performed by MLST. Clinical information, antimicrobial susceptibility and the mechanisms of carbapenem and colistin resistance were analysed. Transmissibility of the carbapenem-resistance determinants was examined by conjugation experiments. Results: The main source of A. seifertii BSI was the respiratory tract (46.3%). The 28 day and in-hospital mortality rates of A. seifertii BSI were 18.8% and 30.0%, respectively. High APACHE II scores and immunosuppressant therapy were independent risk factors for 28 day mortality. The most common MLST type was ST553 (58.8%). Most A. seifertii isolates were susceptible to levofloxacin (86.2%), and only 37.5% were susceptible to colistin. Carbapenem resistance was observed in 16.3% of isolates, mostly caused by the plasmid-borne IS Aba1-bla OXA-51 -like genetic structure. A. seifertii could transfer various carbapenem-resistance determinants to A. baumannii, Acinetobacter nosocomialis and other A. seifertii isolates. Variations of pmrCAB and lpxCAD genes were not associated with colistin resistance of A. seifertii . Conclusions: Levofloxacin and carbapenems, but not colistin, have the potential to be the drug of choice for A. seifertii infections. A. seifertii can transfer carbapenem-resistance determinants to other species of the A. baumannii group and warrants close monitoring.